Hidrocarbonetos policíclicos aromáticos na plataforma continental de Fortaleza, CE: distribuição espacial, variação sazonal e fontes - Martins, Davi de Araújo (2019)
This paper analyzes the levels of polycyclic aromatic hydrocarbons in order to evaluate the quality of marine surficial sediments present in the internal continental shelf of Fortaleza. For this, the samples were extracted, purified, and injected in a gas chromatograph-mass spectrometer. The 16 priority concentration PAHs sum ranged from 2.51 (S3c) to 25.89 (S10c) in the rainy season and 5.60 (S7s) to 25.37 (S13s) ng.g- 1 in the dry season. The %Per/Σ5 rings ratio was used to distinguish between natural and anthropogenic inputs in marine sediments. The majority stations indicated a natural contribution. Molecular ratios Fltr/Pir, BaA / (BaA + Cri), IcdP / (IcdP + BghiP), Fen/Ant were used to distinguish PAHs (petrogenic or pyrolytic) sources. These relationships indicated that, mostly, the origin of PAHs present in sediments is pyrolytic. For the estimation of ecological risk, all stations were below the threshold effect level regulated by the Canadian Council of Environment Ministers for marine sediments.